Loss of Vac14, a regulator of the signaling lipid phosphatidylinositol 3,5-bisphosphate, results in neurodegeneration in mice - Zhang, Yanling (National Academy of Sciences, 2007)
The signaling lipid, phosphatidylinositol 3,5-bisphosphate (PI(3,5)P(2)), likely functions in multiple signaling pathways. Here, we report the characterization of a mouse mutant lacking Vac14, a regulator of PI(3,5)P(2) synthesis. The mutant mice exhibit massive neurodegeneration, particularly in the midbrain and in peripheral sensory neurons. Cell bodies of affected neurons are vacuolated, and apparently empty spaces are present in areas where neurons should be present. Similar vacuoles are found in cultured neurons and fibroblasts. Selective membrane trafficking pathways, especially endosome-to-TGN retrograde trafficking, are defective. This report, along with a recent report on a mouse with a null mutation in Fig4, presents the unexpected finding that the housekeeping lipid, PI(3,5)P(2), is critical for the survival of neural cells.